Epigenetic modifications precede molecular alterations and drive human hepatocarcinogenesis - Carolin Czauderna; Alicia Poplawski; Colm J. O’Rourke; Darko Castven; Benjamín Pérez-Aguilar; Diana Becker; Stephanie Heilmann-Heimbach; Margarete Odenthal; Wafa Amer; Marcel Schmiel; Uta Drebber; Harald Binder; et al. (JCI Insight, 2021)
Development of primary liver cancer is a multistage process. Detailed understanding of sequential epigenetic alterations is largely missing. Here, we performed Infinium Human Methylation 450k BeadChips and RNA-Seq analyses for genome-wide methylome and transcriptome profiling of cirrhotic liver (n = 7), low- (n = 4) and high-grade (n = 9) dysplastic lesions, and early (n = 5) and progressed (n = 3) hepatocellular carcinomas (HCC) synchronously detected in 8 patients with HCC with chronic hepatitis B infection. Integrative analyses of epigenetically driven molecular changes were identified and validated in 2 independent cohorts comprising 887 HCCs. Mitochondrial DNA sequencing was further employed for clonality analyses, indicating multiclonal origin in the majority of investigated HCCs. Alterations in DNA methylation progressively increased from liver cirrhosis (CL) to dysplastic lesions and reached a maximum in early HCCs. Associated early alterations identified by Ingenuity Pathway Analysis (IPA) involved apoptosis, immune regulation, and stemness pathways, while late changes centered on cell survival, proliferation, and invasion. We further validated 23 putative epidrivers with concomitant expression changes and associated with overall survival. Functionally, Striatin 4 (STRN4) was demonstrated to be epigenetically regulated, and inhibition of STRN4 significantly suppressed tumorigenicity of HCC cell lines. Overall, application of integrative genomic analyses defines epigenetic driver alterations and provides promising targets for potentially novel therapeutic approaches.